Prognostic and therapeutic role of damps in critical care illness - Faura, Júlia; Bustamante, Alejandro; Montaner, Joan (Journal of Emergency and Critical Care Medicine; Vol 2 (December 2018): Journal of Emergency and Critical Care Medicine, 2018)
In critical care illness, such as trauma, cardiac arrest or central nervous system (CNS) injury, tissue destruction exposes molecules that act as danger signals. These signals activate the innate immune system and initiate the immune response. However, this immune response can entail many complications for patients in intensive care units (ICUs). Hence, the danger signals, called damage-associated molecular patterns (DAMPs), could take part and be important in the prognosis of these patients either as biomarkers or as therapeutic targets (1).